Good Fences Make Good Governments - Veroneau, John (Maine Policy Review, 2024)
In this issue's Margaret Chase Smith Essay, Ambassador John K. Veroneau describes a new paradigm that he believes is needed to rejuvenate our society, rebuild trust in our government, and renew pride in our country. Whatever its contours, this new paradigm will create a new equilibrium and establish for another long period of time what Americans should expect from government and from each other.
Keywords: governing model; limited government; federal government